Social and occupational outcomes for young people who attend early intervention mental health services: a longitudinal study. Issue 2 (18th October 2021) - Iorfino, Frank; Carpenter, Joanne S; Cross, Shane PM; Crouse, Jacob; Davenport, Tracey A; Hermens, Daniel F; Yee, Hannah; Nichles, Alissa; Zmicerevska, Natalia; Guastella, Adam; Scott, Elizabeth M; Hickie, Ian B
Abstract: Objective: To identify trajectories of social and occupational functioning in young people during the two years after presenting for early intervention mental health care; to identify demographic and clinical factors that influence these trajectories. Design: Longitudinal, observational study of young people presenting for mental health care. Setting: Two primary care‐based early intervention mental health services at the Brain and Mind Centre (University of Sydney), 1 June 2008 – 31 July 2018. Participants: 1510 people aged 12‒25 years who had presented with anxiety, mood, or psychotic disorders, for whom two years' follow‐up data were available for analysis. Main outcome measures: Latent class trajectories of social and occupational functioning based on growth mixture modelling of Social and Occupational Assessment Scale (SOFAS) scores. Results: We identified four trajectories of functioning during the first two years of care: deteriorating and volatile (733 participants, 49%); persistent impairment (237, 16%); stable good functioning (291, 19%); and improving, but late recurrence (249, 16%). The less favourable trajectories (deteriorating and volatile; persistent impairment) were associated with physical comorbidity, not being in education, employment, or training, having substance‐related disorders, having been hospitalised, and having a childhood onset mental disorder, psychosis‐like experiences, or a history of self‐harm or suicidality. Conclusions: Two in three young people with emerging mental disorders did not experience meaningful improvement in social and occupational functioning during two years of early intervention care. Most functional trajectories were also quite volatile, indicating the need for dynamic service models that emphasise multidisciplinary interventions and measurement‐based care.